Cognitive load in multimedia learning environments: A systematic review - Mutlu-Bayraktar, Duygu; Cosgun, Veysel; Altan, Tugba (Computers and education, 2019)
The purpose of this study was to review articles involving cognitive load and multimedia learning between 2015 and 2019 in a systematic way. 94 articles were reviewed in terms of the types of cognitive load, multimedia learning principles, cognitive load measurements, the investigated dependent and independent variables, cognitive processes, the types of multimedia learning environments and the demographic characteristics of the studies. The results revealed that reviewed studies indicated the type of cognitive load seem to have investigated the extraneous cognitive load more frequently. The most studied multimedia learning principles in reviewed articles were modality principle, seductive details effect and signaling/cueing principle respectively. Most reviewed cognitive load studies on multimedia learning were conducted by researchers in Europe, especially in Germany, followed by Asia, America, Australia, and Africa. Research results showed that most cognitive load studies in multimedia learning environments conducted thus far have utilized STEM subjects. Higher education students were the primary participant group in the cognitive load in multimedia learning research as well. There was a tendency to use subjective methods more often than objective methods to measure cognitive load in investigations. In addition to cognitive load, learning, prior knowledge, and motivation were measured most frequently in these studies. In the reviewed studies, multimedia design, material type, presentation format, and individual differences were the most selected focus of research. Research results were interpreted and a number of gaps in cognitive load research relating to multimedia learning were identified. •Cognitive load studies investigated the extraneous cognitive load more frequently.•Subjective methods have been used more often than objective methods.•Most preferred focus of researches were multimedia design and presentation format.•Cognitive Load studies were popular in higher education for STEM subjects.•Modality, seductive details, and signaling were most studied principles.